Nurses’ Involvement In Health Care Research and Policy Development in the Context of Mother-to-Child HIV/AIDS Transmission in Nigeria. - Asuquo, Ekaete Francis (Université d'Ottawa / University of Ottawa, 2016)
The reduction of disease burden in the context of mother-to-child HIV transmission in Nigeria invokes a multi-sectoral and multi-disciplinary approach, which incorporates using research evidence to promote relevant policies. Nurses as health workers play a central role in health sector responses to ameliorate disease burdens such as those affiliated with HIV. Situated within critical social theory and using theoretical perspectives on power, this qualitative study examines the extent of nurses' contributions to research production and policy development in mother-to-child HIV transmission in the Cross River State, Nigeria. The study was guided by four specific objectives: 1) to assess nurses’ knowledge of current global strategies; 2) to describe nurses’ contributions to research and policy development; 3) to identify issues that encourage or impede the involvement of nurses in research and policy development and ;4) to identify promising models to actively engage nurses in research and policy development. A case study approach and participatory action research methodologies facilitated a comprehensive examination of the extent of Nigerian nurses' research and policy involvement and provided collective action for change. Interviews, document reviews, and focus group discussions were methods utilized for data collection and validation of collected data. Four major themes emerged: intimate knowledge of healthcare, marginal involvement in knowledge creation, limited involvement in mother-to-child transmission (MCTC) policy decision making and going with the flow. The study findings revealed that the nurses had good knowledge of local/global HIV trends, MTCT ameliorating strategies, barriers to MTCT uptake, processes of mobilizing local strategies, and an in-depth understanding of the integral role of implementing partners and the nursing workforce in ameliorating the impact of HIV on mother and child. However, this intimate knowledge did not translate into knowledge creation through independent research productivity in this context. The study further revealed that nurses were mostly involved in data collection and validation of collected data, which was not leading to publications. Barriers to knowledge creation included individual or personal constraints, as well as institutional and systemic barriers. Solving this problem requires funding of research studies, building research capacity, mentoring, earmarking research grants for nurses, increasing budgetary allocations to research, creating research awareness, creating a stimulating research environment with computers and internet access, using research as a criterion for promotion, and providing incentives. The study also revealed the insignificant participation of nurses in policy decision making, with involvement limited to implementation of PMTCT policy. Barriers to nurses' involvement in decision-making emanated from individual and health care system constraints, and nurses' contributions to decision making can only be improved by educational upgrading, integrating policy courses into nursing curricula, mentoring, group advocacy, involvement in politics, and organizational restructuring. The study showed that nurses were generally complacent about their involvement in knowledge creation and policy development. They tended to move with the flow of events and were afraid to question the status quo. A tree animation nursing (TAN) model provided a promising model for change with four main components:1) university education, 2) strong nursing leadership, 3) the identification of barriers, 4) and envisioned solutions, all of which are necessary to enable nurses to actively engage in research productivity and policy formulation. University education is recommended as a prerequisite for all nurses, and policies that foster a culture of nursing research productivity and policy development should be promoted.
Keywords: Nurses; Research; Policy; PMTCT; Nigeria